2008
DOI: 10.1557/proc-1094-dd06-05
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled Materials Containing Complementary Nucleobase Molecular Recognition

Abstract: Here we report the nucleic acid/cationic amphiphile based-materials in which we exchange the counter-ions of the polyanionic backbone of the nucleic acids with the cationic amphiphiles to form self-assembled transparent films with the thickness of several microns. Predominantly, single stranded poly(A), poly(U) and double stranded poly(AU) were employed for these studies. Small-angle X-ray scattering (SAXS) experiments suggested lamellar-like structure for all the film samples. However, the molecule length as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…Both supramolecular films, DNA-DDAB and PSS-DDAB at 30mm-thickness appear to be transparent. Based on comparison with previous works, [17][18][19] we found that in the multi-lamellar structure of the supramolecular film layers of the polyanion (DNA and presumably PSS) are separated by lipid bilayers of DDAB. The hydrophobic interactions among the double alkyl tails of DDAB molecules are probably responsible for the lipid bilayer formation within the film.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…Both supramolecular films, DNA-DDAB and PSS-DDAB at 30mm-thickness appear to be transparent. Based on comparison with previous works, [17][18][19] we found that in the multi-lamellar structure of the supramolecular film layers of the polyanion (DNA and presumably PSS) are separated by lipid bilayers of DDAB. The hydrophobic interactions among the double alkyl tails of DDAB molecules are probably responsible for the lipid bilayer formation within the film.…”
Section: Resultssupporting
confidence: 55%
“…The hydrophobic interactions among the double alkyl tails of DDAB molecules are probably responsible for the lipid bilayer formation within the film. [17][18][19][20] The contents of carbon, hydrogen and nitrogen in the film were determined by elemental analysis, which confirms that the obtained films were formed in a one to one stoichiometry of an anionic polymer and a cationic amphiphile: DNA-DDAB film C 58%, H 11% and N 8% (theoretical calculation C 56%, H 9% and N 9%) and PSS-DDAB film C 67%, H 11% and N 3% (theoretical calculation C 64%, H 10% and N 2%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent synthesis of particle building blocks functionalized with specifically designed oligonucleotides has provided new possibilities for the assembly of networked materials. [1][2][3][4][5][6][7][8][9] The varied applications of polymer microspheres benefit from precise control over surface chemistry. Grafted molecules or functional groups determine the rheology 10 and stability of the colloids used in pastes and coatings, influence the self-organization of the dense suspensions used in materials synthesis, and provide specific biomolecular binding sites for biological assays and cell adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…3,[18][19][20][21][22][23][24] Nucleic acids can also be used as a bulk material for a new type of biomaterial based on DNA/RNAsurfactant solid films. 4,5,25 General assembly methods for DNA are based on the use of covalent linker molecules which possess alkanedithiol functionalities at opposing ends with chemical affinities towards gold particles. 26,27 The thiol groups present at the end of the linker molecule are covalently attached to the gold colloidal particles and this facilitates aggregation upon binding to the complementary sequence.…”
Section: Introductionmentioning
confidence: 99%